The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1139/v81-486
|View full text |Cite
|
Sign up to set email alerts
|

High resolution nuclear magnetic resonance studies of platinum(II) – guanosine-5′-monophosphate interactions in aqueous solutions

Abstract: A detailed 400 MHz 1H nmr study was carried out on platinum complexation products of GMP by K2PtCl4. Coupling constant values show that platination on N7 induces a conformational change on the ribose moiety: the 3E form of the ring and the gt conformer about the C(4′)—C(5′) bond are favoured upon complexation. The results are compared to the conformational changes induced by N7 protonation and methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Substitution of a large atom such as Br (7) or a bulky organic substance such as 2-(acetylamino)fluorene (carcinogen) (8) at the C-8 position of the guanine moiety or a negative group such as PtCl3 at N 7 could facilitate the B to Z transition. It has been shown that the coordination of metal cations such as the Mg(II) ion (9,10,11), the [Co(NH 3 ) 6 ]+ 3 (11 ,12) and the PtCl3 group (13) to the N 7 -site of the guanine base also can bring about the B to Z transition.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of a large atom such as Br (7) or a bulky organic substance such as 2-(acetylamino)fluorene (carcinogen) (8) at the C-8 position of the guanine moiety or a negative group such as PtCl3 at N 7 could facilitate the B to Z transition. It has been shown that the coordination of metal cations such as the Mg(II) ion (9,10,11), the [Co(NH 3 ) 6 ]+ 3 (11 ,12) and the PtCl3 group (13) to the N 7 -site of the guanine base also can bring about the B to Z transition.…”
Section: Introductionmentioning
confidence: 99%
“…Raman and nmr spectroscopy I has often been used (1,2,(5)(6)(7)(8) to characterize the nature of such electrophilic interaction with mono-and polynucleotides, whereas ir is the least used technique for this purpose, so far (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This slow equilibrium is characterized by distinct signals for the involved sugar protons, and their relative populations may be calculated only from their signal integrals, resulting in nearly equal percentages. Regarding the gg conformation about the bond C4′–C5′, although a decrease in the gg percentage was expected [ 48 ], it appears to be practically stable for [ 1 -guo] and [ 2 -guo]A, while it is slightly lower for [ 2 -guo]B. In other words, the platination of guo by ( 1 ) and ( 2 ) does not practically affect the conformation around the C4′–C5′ bond compared to free guanosine.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the [2-guo]B adopts a more pronounced tendency for anti-conformation (93%), which may induce greater distortion in the DNA helix. a,b Taken from reference [48] and [36], respectively.…”
Section: Sugar Conformation Analysismentioning
confidence: 99%
See 1 more Smart Citation